Tax Preferences for Environmental Goals Use, Limitations and Preferred Practices - Greene, James (OECD Environment Working Papers, 2014)
This paper reviews the use of tax preferences to achieve environmental policy objectives. Tax preferences involve using the tax system to adjust relative prices with a view to influencing producer or consumer behaviour in favour of goods or services that are considered to be environmentally beneficial. They take various forms, typically a partial or total exemption from a specified tax. Because tax preferences help to avoid or reduce costs for businesses or consumers, there are often pressures on governments to favour them over other instruments. As a result, they are sometimes used inappropriately, typically to address negative externalities for which they are not well suited. The paper suggests that the comparative advantage of tax preferences is in providing support for positive externalities, that is situations in which a subsidy would help to deliver more social benefits than would otherwise be the case. When designing tax preferences, care must be taken to ensure that they do not encourage technological lock-in, provide perverse incentives for environmentally harmful activities (the rebound effect), or reward producers or consumers for actions they would have taken anyway. Since tax preferences are a form of subsidy, they should be subject to the same degree of scrutiny and oversight as other forms of public expenditure